The Function of Sea References in Certain Plays of Racine - Lynch, Karen J. (My University, 1974)
This study is an investigation of the function of sea references in certain plays of Racine, particularly as these sea references relate to the three classical unities of time, place and action.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures